Viral Hepatitis Delta: An Underestimated Threat (Texas Journal of Medical Science, 2023)
In the world, there are more than 350 million people infected with the hepatitis B virus, of which 15-25% (750 thousand) die each year due to the development of complications of liver cirrhosis and hepatocellular carcinoma. The proportion of patients with HBV who have a concomitant delta agent that dramatically complicates its natural course varies from less than 1% to more than 10% in different populations. Worldwide, 20 million people may be infected with hepatitis delta virus. According to expert estimates in the Republic of Uzbekistan, screening studies in risk groups in 2014 revealed the presence of HBsAg in 2.3% of the population. Among pregnant women and blood donors, the prevalence of HBV is 1.3% in 2021 and 1.2% in 2022, respectively. Given the fact that HDV RNA cannot replicate without contamination by HBsAg, the endemicity of HDV should directly depend on the prevalence of HBV in the country. However, according to current epidemiological studies, this relationship is not natural and the areas of circulation of the delta agent do not correspond to the prevalence of HBV.